Optimalisasi Alur Kerja Pengambilan Material Processor dengan Metode Lean Manufacturing Pada PT. XYZ - Erzon, Elvi Anggino; Mochammad Tutuk Safirin (Jurnal Serambi Engineering, 2025)
A company's warehousing has a significant impact on the smooth flow of materials, both in storage and in distribution. An effective warehousing system ensures that materials are available on time and in the required condition. The implementation of lean manufacturing in warehouse management aims to reduce waste and improve operational efficiency. This study was conducted in the warehouse of PT XYZ, which was facing challenges in the material picking workflow due to sub-optimal storage layouts. The methods used included initial workflow analysis, waste identification and the application of lean manufacturing strategies such as storage centralisation and layout optimisation. The results showed that this approach successfully reduced material retrieval time from 12 minutes to 8 minutes and travel distance from 173 metres to 115 metres. In addition, storage space requirements were minimised by freeing up several racks for other materials. The implementation of Lean Manufacturing has significantly improved PT XYZ's warehouse productivity by creating a more efficient and organised workflow.